Strategis Pengembangan The Great Asia Afrika Sebagai Destinasi Wisata di Bandung - Rizki Nurul Nugraha; Devitha Sondang (Peneliti.net, 2023)
Based on Law No.10 of 2009 concerning tourism, it is stated that tourism development is needed to encourage equal opportunities to try and obtain benefits and be able to face the challenges of changing local, national, and global lives. Tourism development strategies are very important in planned tourism so that their strengths can be developed effectively. The great asia africa development strategy opens up opportunities for surrounding communities to earn income through tourist attractions in the great asia africa. The impact of this study aims to improve the management of the tourism sector in Indonesia through strategies carried out by the government and community participation in the development of Indonesian tourism. This journal is compiled using qualitative methods. This research discusses the stratgei of development at The Great Asia Afrika located in Lembang, Bandung.